Direct Oral Anticoagulants in Patients Undergoing Urgent Reperfusion for Nonvalvular Atrial Fibrillation-Related Ischemic Stroke: A Brief Report on Literature Evidence - Luca Masotti; Elisa Grifoni; Alessandro Dei; Vieri Vannucchi; Federico Moroni; Grazia Panigada; Costanza Nicotra; Stefano Spolveri; Giancarlo Landini (Neurology Research International)
Introduction. The optimal timing for starting anticoagulation in the early phase of nonvalvular atrial fibrillation (NVAF)-related acute ischemic stroke (AIS) remains a challenge, especially in patients undergoing urgent reperfusion by systemic thrombolysis or mechanical thrombectomy. The aim of our study was to review the literature evidence reporting on safety of direct oral anticoagulants (DOACs) starting in the early phase of NVAF-related AIS undergoing systemic thrombolysis and/or mechanical thrombectomy. Materials and Methods. We reviewed the PubMed databases searching articles reporting on efficacy and safety of DOACs starting time within two weeks from AIS onset in patients undergoing systemic thrombolysis and/or mechanical thrombectomy. Results. Three studies were selected, overall including one hundred and six patients (62 females, 58.4%). Median National Institute of Health Stroke Scale (NIHSS) score at hospital admission ranged from 9 to 13 points. Median DOACs starting time ranged from 2 to 6 days. Median CHA2DS2-VASC score ranged from 4 to 6 points. Follow-up was limited to 14 days in one study, 30 days in another, and 90 days in a third one. Overall, stroke recurrence and/or intracranial bleeding occurred in two patients (1.9%) and no patient died at follow-up. Conclusion. Small sample size real life studies seem to demonstrate that the introduction of DOACs in the early phase of NVAF-related AIS undergoing urgent reperfusion is efficacious and safe. Prospective RCTs are necessary to confirm these findings.